La Profesionalización De La Docencia Universitaria Y Su Influencia En El Desarrollo De Las Competencias Pedagógicas En La Formación De Docentes En El Instituto Superior De Ciencias De La Educación (ISCED) De Benguela, Angola - Alonso-García, Santiago; Sánchez-Vega, Elena; Inocêncio, Ernesto (European Scientific Journal, ESJ, 2017)
The presentation of the results of the present study was used to fundamentally analyze the influence of professionalism of university teaching in the development of the pedagogical competences of students in teacher training at the Higher Institute of Educational Sciences (ISCED) in Benguela. This study was carried out on the theme based on reference. The research carried out is of the descriptive type, whose data collection was quantitative and qualitative, from the determined sample. It is made up of teachers, students, and school board members. This, however, is a quantitative and qualitative study. Based on the data collected, the paper concludes on the lack of planning in pairs of the teaching work, the lack of a specific team for the supervision of the teaching work, and the fact that there is no specific criterion in the entrance periphery of teaching candidates.